THE YUGOSLAV NATIONAL FRONT: ATTEMPT(S) TO UNIFY THE YUGOINTEGRALISTS EXTREME RIGHT 1935–1939 - Dragosavljevic, Vasilije (Serbian political thought, 2024)
The idea of ​​forming the Yugoslav National Front was the reaction of supporters of national and state unitarism to the gradual federalization of the first Yugoslav state initiated by the government of the Yugoslav Radical Union. The concept of a national front arose in the ranks of the senatorial club of the Yugoslav Radical Peasant Democracy party, and over time, other Yugoslav integralist political organizations accepted it – the Yugoslav People’s Party, the YNM Zbor, and several political factions that arose in the process of the disintegration of Bogoljub Jevtić’s political group. Contrary to the thesis put forward by socialist historiography that the leading cause of the failure of the concept of the Yugoslav National Front was the struggle for primacy between the leaders of the Yugoslav integralist parties, a detailed analysis shows us that behind the failure was the continuous work of the government of M. Stojadinović on preventing the unification of supporters of integral Yugoslavism. The radical methods used by the regime to achieve this goal (corruption, police repression, negative campaign in the media, construction of false affairs) eloquently testify to the political potential that the idea of ​​gathering all supporters of national and state unitarism had and also to the danger that its implementation represented for the government of M. Stojadinović. There is a paradox in the fact that the concept of the Yugoslav National Front was ultimately implemented by Milan Stojadinović – a person against whose politics the idea itself was directed and who devoted most of the time he spent at the head of the Yugoslav government to the fight against the unification of the Yugoslav integralist forces. At the same time, this paradox (in addition to the instability of Stojadinović’s political principles) clearly illustrates the role of the theory of integral Yugoslavism as the last line of defense for the integrity of the Yugoslav state in moments of crisis.